Sugarcane Biomass Production in South Florida: A Comparative Emergy Assessment of Organic Soil and Mineral Soil Production Systems - Amponsah, N.Y.; Hanlon, E.A.; Izursa, J.L.; Capece, J.C. (Journal of Environmental Accounting and Management, 2026)
An Emergy Assessment (EMA) of sugarcane cultivation as feedstock for bioethanol production in South Florida was performed to develop a sustainability profile of the farming systems. In this study, a sugarcane farming system on muck soil (organic soil) was compared with a similar cropping system on a sandy soil (mineral soil). The study provides a comparison of these alternative systems from the perspective of their resource use, environmental impact and sustainability. The representative farm for both systems was based on a 5000 acre farm assumed to be already established in South Florida. Emergy analysis was applied to evaluate environmental support required for the sugarcane production in both systems. In line with the methodology a quantitative inventory of free natural resources and purchased input flows into the systems was created. The results showed that aside ground water irrigation which dominates (44%) in both systems, the largest emergy flows for biofuel production on organic soil were associated with soil erosion or subsidence (19%), labor (12%), evapotranspiration (11%), and fuel (8%). However, for sandy soil production, the main contributors were lime (13%), labor (12%), and fuel (8%). The emergy analysis suggests that due to the non-renewability of soil loss in the organic soil farming system, a reduction in the purchased inputs for sandy (mineral) soils based on alternative farming measures potentially makes mineral soil sugarcane ethanol production a rather more sustainable and attractive alternative for a better environmental performance.